Pengaruh Penambahan Semen Portland Terhadap Sifat Mekanik Geopolimer Berbasis Fly Ash - Muin, Nurfajriani; Subaer,; Nurhayati, (JFT: Jurnal Fisika dan Terapannya, 2024)
This study is a pure experimental research aimed at investigating the influence of adding portland cement on the mechanical properties of fly ash-based geopolymers. The composites were synthesized using fly ash as the base material, along with portland cement and alkali activation. Four compositions of samples were prepared with varying additions of portland cement at 0%, 20%, 40%, and 60%. The samples were then cured at 70°C for 2 hours and subsequently stored in an open space for 28 days. The crystal structure of the samples was analyzed using X-Ray Diffraction (XRD). Fourier Transform Infrared (FTIR) was used to examine the functional groups in the samples. Density and porosity testing were conducted using Archimedes' principle. Meanwhile, the mechanical properties of the samples were tested for compressive and flexural strength. The results of the XRD analysis showed the presence of quartz (SiO2) crystal peaks, along with other phases formed, including Calcium Oxide, Calcium Aluminum Silicate, Sodium Aluminum Silicate, Iron Oxide, Calcium Peroxide, and Aluminum Iron Oxide. The FTIR analysis of the composite functional groups indicated that there were no significant shifts in the absorption bands' wave numbers (cm-1) for each composition variation. The test results for density, porosity, and mechanical properties of the samples demonstrated a decrease with increasing additions of portland cement. The most optimal formulation was the geopolymers without the addition of portland cement (G-PCC 0%), which exhibited the highest compressive strength and relatively higher flexural strength.